ISOLASI CENDAWAN RHIZOSFER PELARUT FOSFAT PADA JABON MERAH (Neolamarckia macrophylla) PROVENANS KABUPATEN SIDRAP SULAWESI SELATAN - Alif, Alisyah Andini; Gusmiaty, G; Akzad, Muhammad Bima; Rahim, Iradhatullah; Larekeng, Siti Halima (Jurnal Galung Tropika, 2023)
This research aims to determine the total chlorophyll of jabon merah leaves extract using acetone and ethanol solvent and to determine the difference in total chlorophyll of jabon merah leaves extract using acetone dan ethanol solvent. The result of the analysis of chlorophyll levels in the extraction of jabon merah leaves using the SPAD-502 method showed that the base and the middle of the jabon merah leaf were the part that had the highest chlorophyll content, and the tip of the jabon merah leaf has a lower chlorophyll content. In the spectrophotometric method using acetone solvent, the result of chlorophyll a is 34.543,9 mg/L, and chlorophyll b is 30.338,6 mg/L. The result of chlorophyll using ethanol solvent is 33.171,8 mg/L for chlorophyll a and 19.065,9 mg/L for chlorophyll b. The total chlorophyll content in jabon merah leaves with acetone solvent is 65,346,4 mg/L, and for ethanol solvent, ia 52.474 mg/L. The results show that acetone is a good solvent for extracting jabon merah leaves.